Transcranial Magnetic Stimulation in Succinic Semialdehyde Dehydrogenase Deficiency: A Measure of Maturational Trajectory of Cortical Excitability. (November 2021) - Tsuboyama, Melissa; Liu, Jingjing; Kaye, Harper; DiBacco, Melissa; Pearl, Phillip L; Rotenberg, Alexander
Background: Succinic semialdehyde dehydrogenase deficiency (SSADHD) is a disorder of GABA degradation with use-dependent downregulation of postsynaptic GABAA/B receptors. We aim to measure the resulting cortical excitation: inhibition ratio using transcranial magnetic stimulation. Methods: In this single-center observational study, 18 subjects with SSADHD and 8 healthy controls underwent transcranial magnetic stimulation. Resting motor threshold, cortical silent period, and long-interval intracortical inhibition were measured in both groups. Resting motor threshold in focal epilepsy patients from an institutional transcranial magnetic stimulation database were also included. Results: SSADHD subjects had higher resting motor threshold than healthy controls but lower relative to focal epilepsy patients. Resting motor threshold decreased with age in all groups. Cortical silent period was longer in SSADHD subjects than in healthy controls. No difference was detected in long-interval intracortical inhibition between the 2 groups. Conclusion: Findings suggest abnormal corticospinal tract physiology in SSADHD, but with preserved developmental trajectory for corticospinal tract maturation. Defining features of these transcranial magnetic stimulation metrics in SSADHD will be better elucidated through this ongoing longitudinal study.